Solvent-free microwave-assisted synthesis of imidazo[1, 5- a]pyridine and –quinoline derivatives. Issue 21 (2nd November 2019) - Herr, Jasmin Martha; Rössiger, Carina; Albrecht, Georg; Yanagi, Hisao; Göttlich, Richard
Abstract: A quick and highly efficient microwave-assisted preparation of imidazopyridines and –quinolines is described, starting from the corresponding ketones and amines. The method requires no solvent and uses activated MnO2 as an oxidant. A mechanism for the cyclization is proposed and discussed. Graphical Abstract: